Preparing for Success Program (non-award enabling program). - Taylor, Janet A.; van Eyk, Tina (Australia. Dept of Education and Training (DET), 2018)
This case study report for project SP14-4602 describes the impact of completing the enabling program, Preparing for Success Program (PSP) at Southern Cross University (SCU) on student experience in undergraduate study. Students who completed PSP and who were now enrolled in the second year of their degree studies were interviewed. The interview data were coded using both grounded theory and Kahu’s framework. The interviews revealed that completing PSP had significant impact on the students’ undergraduate experience. The students were more confident, possessed the necessary academic skills including management of lifeload and felt a sense of belonging in their undergraduate studies. Quantitative institutional data and staff interview responses confirmed the success of PSP students in their undergraduate studies. A summary of the case study is also available, published as: Enabling pathways lead to successful outcomes.